Análisis jurídico de la Ley Orgánica del Sistema Nacional de Contratación Pública relacionada al sector de la construcción - Tapia González, Cristina Yaniva (2009)
This work, whose title is " Legal Analysis of the Organic Law of the National Procurement related to the construction sector”, is a legal study of the principles and governing public procurement in our country, like: Legality, Concurrence, Transparency, Effective Technology, Equality, Generality and Universality. In his intent to let know the addition the new definitions and system tools, with to make a differentiation with the previous legal system and the legal principles applied to the contracts with the State, to determine the advantages and disadvantages of implementing the new system in the public construction contracts. Furthermore, he analyses the common rules for public procedures and dynamic procedures in order to establish their profits and losses on contracts related to construction.